Self-administration and Reliability of Computerized Neurobehavioral Tests among Egyptian Pesticide Workers - Fayssal M. Farahat (Journal of High Institute of Public Health, 2007)
Background: Behavioral Assessment and Research System (BARS) is a computer-based test system designed to assess neurobehavioral function and neurotoxicity in humans. This system is available in 5 languages including Arabic. Objectives: To assess the potential use of the Arabic version of computerized neurobehavioral system (BARS) and to compare performance of Egyptian pesticide workers to non-exposed populations using the same computerized battery. Methods: This study involved the administration of eight neurobehavioral tests from the Arabic computerized neurobehavioral test battery (BARS) to Egyptian workers occupationally exposed to pesticides (n= 25) as compared to non-exposed Egyptian workers (n= 25). One-week test-retest reliability of the computerized battery was measured among non-exposed participants. Results: Performance of pesticide non-exposed Egyptian workers did not show any significant differences between test and re-test (i.e. after one week). Performance of pesticide exposed workers was significantly lower in most of the administered computerized tests as compared to non-exposed Egyptian and US populations. Conclusions: The current findings demonstrate the potential utility of the Arabic computerized BARS in occupational epidemiological research especially in the short-term intervals. Stability of the administered Arabic BARS tests over the short-term interval makes it broadly applicable in assessing exposures at different workplaces and with different cultural and educational levels.